Endomyocardial biopsy in Chagas' heart disease: pathogenetic contributions - Higuchi, Maria de Lourdes (1995)
Endomyocardial biopsy procedure has been performed in many centers around the world, allowing a better treatment and follow up of the patients with myocardial disease. In Chagas' disease, it has been performed in São Paulo Heart Institute since 1978 and has brought important contributions to the understanding of the disease and consequently of the patient's clinical stage. In the present work we summarize the principal findings regarding the pathogenesis of Chagas' disease obtained mainly from the studies using endomyocardial biopsy specimens. Nowadays we do not have doubts that the inflammatory infiltrate aggressing myocardial fibers has fundamental role in the progression of the myocardial damage in Chagas' disease what culminates in chronic heart failure. The parasite seems to have active participation in the maintenance of such myocardial inflammation.